Pengembangan Media Prezi Pada Kemampuan Menulis Teks Cerpen Kelas XI - Wahyuni, Luluk Sri (Ruang Kata, 2024)
The research aims to design and test the validity and feasibility of Prezi-based learning media in improving short story text writing skills for grade XI high school students. Prezi media was chosen because it is considered effective in attracting students' interest and facilitating a more interactive classroom environment. It is expected that the use of this media can help students in developing writing skills, especially in creating short story texts. The research and development process follows the five stages in the Dick and Carry (ADDIE) model, namely analysis, design, development, implementation, and evaluation. Data were collected through validation by media and material experts, as well as through student responses. Media testing was conducted in class XI of SMA Negeri 1 Bubulan. The results of data analysis showed that the Prezi media designed was considered good and feasible to use, based on the assessment of media experts, material experts, and student responses. The validation by media experts showed a feasibility of 75% with an average score of 3 in the media quality aspect, while the material expert validation showed a feasibility level of 85% with an average score of 3.4. Scientifically, this learning media is proven to be effective and can be applied in learning, especially in short story text writing skills